What is Error Analysis, and How Can It Be Used in a Mathematics Classroom? - Mallue, Tyler (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Everyone makes mistakes, but the important part of mistake making is learning and growing after having made the mistake. Mistakes can reveal a lot about the thinking process, and this is valuable information for educators. Instead of treating mistakes as negative events in a student’s progress, they can instead be thought of as helpful and critical tools in the learning process. The important question to answer is how teachers can use student errors to successfully create learning opportunities for their students. Teachers can use error analysis in several ways, to diagnose misunderstandings, initiate discussions, and as a starting point for revealing and clearing up misconceptions. Error analysis can create unique learning opportunities for students and should be utilized by teachers.